1935
DOI: 10.1021/ja01312a039
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of l-Arabinal to l-Erythrose1

Abstract: In a previous paper2 it was shown that «/-xylal by means of ozone could be degraded to a tetrose, which was identified as «/-threose. Ozone apparently had a dualistic action. Firstly, it was added to the double bond, forming an unstable ozonide, which in turn was broken down under the influence of the solvent, acetic acid, to two aldehyde groups. Secondly, cleavage of the 1,5oxygen ring took place, a fact which had to be assumed since a free tetrose and not its 4-formyl derivative was found as the reaction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1935
1935
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Measurements of acid were made by titrating with N/10 NaOH using phenolphthalein as an indicator. The pH was determined by the use of nitrazine paper followed by spot tests (8,9) with indicator solutions when the pH was below 5.2. Aliquots removed before titration were used for making counts.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of acid were made by titrating with N/10 NaOH using phenolphthalein as an indicator. The pH was determined by the use of nitrazine paper followed by spot tests (8,9) with indicator solutions when the pH was below 5.2. Aliquots removed before titration were used for making counts.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown by him that when pneumococcus antiserum is diluted with distilled water, the major portion of the antibodies separates as an insoluble precipitate. Not only can the immune bodies be precipitated by this means, but they can be effectively separated from the serum by dilution with small quantities of ethyl alcohol (5). The conditions under which antibodies can best be separated from antiserum have been thoroughly investigated (6) and the product which has been isolated has been found to have properties which definitely characterize it as a globulin more basic than ordinary serum globulin (7).…”
mentioning
confidence: 99%
“…The further purification of the water-insoluble globulin bearing the immune bodies of pneumococcus antiserum has also been attempted by Felton (8). It has been shown that fractions of the protein, varying in their solubility in different 179 concentrations of sodium or ammonium sulfate, likewise vary in their capacity to protect mice against infection with standard doses of homologous virulent organisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations